Numerical Investigation on Fracture Mechanisms and Energy Evolution Characteristics of Columnar Jointed Basalts With Different Model Boundaries and Confining Pressures - Wang, Yongyi; Gong, Bin; Tang, Chun’an (Frontiers in Earth Science, 2021)
To reveal the mechanical mechanisms and energy release characteristics underlying progressive failure of columnar jointed basalts (CJBs) with various model boundaries and confining pressures, by combining the meso-damage mechanics, statistical strength theory and continuum mechanics, the images of CJBs with different dip angles to the column axis are constructed and transformed into the inhomogeneous models. In the cases of plane stress, plane strain and between plane stress and plane strain, the gradual fracture processes of CJBs are numerically simulated under different confining pressures, the acoustic emission (AE) energy before and after the peak stress are obtained. The results show that: (1) for the case of plane stress, the fracture process of CJBs along the direction I orthogonal to column axis: at the initial stage of loading, the vertical joints and the transverse joints in the CJBs specimen are damaged; at the late stage of loading, more columns in the middle and upper part of the CJBs specimen are cracked and the failure pattern is formed; (2) for the case between plane stress and plane strain, the fracture process of CJBs along the direction parallel to column axis (β = 30°): at the initial stage of loading, the columnar joints are damaged; at the late stage of loading, the area of damaged and broken columns at the top of the specimen increases and the crushing degree intensifies, and in the upper part of the specimen, several column edges also get damaged; (3) for the AE energy accumulations before the peak stress of CJBs: for the case between plane stress and plane strain, the AE energy accumulation before the peak stress is higher than that the plane strain state along the direction orthogonal to column axis. Meanwhile, along the direction parallel to column axis (β = 30°), the AE energy accumulations before the peak stress becomes larger when changing from the state between plane stress and plane strain to the plane strain state. These achievements will certainly improve our understanding of the fracture mechanism and energy evolution of CJBs and provide valuable insights into instability precursor of CJBs.